Gas plasmas and plasma modified materials in medicine - Cheruthazhekatt, Sadiqali; Černák, Mirko; Slavíček, Pavel (Journal of Applied Biomedicine, 2010)
The applications of gas plasma and plasma modified materials in the emerging fields of medicine such as dentistry, drug delivery, and tissue engineering. Plasma sterilization of both living and non-living objects is safe, fast and efficient; for example plasma sterilization of medical equipment quickly removes microorganisms with no damage to the tiny delicate parts of the equipment and in dentistry it offers a non-toxic, painless bacterial inactivation of tissues from a dental cavity. Devices that generate plasma inside the root canal of a tooth give better killing efficiency against bacteria without causing any harm to the surrounding tissues. Plasma modified materials fulfill the requirements for bioactivity in medicine; for example, the inclusion of antimicrobial agents (metal nano particles, antimicrobial peptides, enzymes, etc.) in plasma modified materials (polymeric, metallic, etc) alters them to produce superior antibacterial biomedical devices with a longer active life. Thin polymer films or coating on surfaces with different plasma processes improves the adherence, controlled loading and release of drug molecules. Surface functionalization by plasma treatment stimulates cell adhesion, cell growth and the spread of tissue development. Plasma applications are already contributing significantly to the changing face of medicine and future trends are discussed in this paper.
Keywords: Sterilization; financování organizované; biomedicínské inženýrství; drug delivery; zubní materiály; biokompatibilní materiály; Prostheses and Implants; sterilization; Metals; Drug Carriers; Polymers; lidé; plasma; chemické jevy; plyny; kovy; zaváděcí katétry; tissue engineering; slitiny; Chemical Phenomena; Financing, Organized; Catheters, Indwelling; Biocompatible Materials; Alloys; Dental Materials; surface functionalization; polymery; sterilizace; nosiče léků; Biomedical Engineering; výzkumné techniky; protézy a implantáty; Investigative Techniques; Gases; dentistry; Humans